Updates on exposure estimation for the Québec cohort of chrysotile miners and millers: implications for risk assessment and threshold hypothesis - Case, Bruce W.; Korchevskiy, Andrey A.; Korchevskiy, Arseniy (Frontiers in Public Health, 2025)
The McGill University cohort of Québec chrysotile miners and millers (total of 11,379 members) has been a major determinant of risk assessment. The U. S. EPA and some other meta-analyses omit this cohort, the largest ever exposed to high concentrations of chrysotile. Preliminary analyses using new data showed average cumulative exposures in the full cohort of 528.5 f/cc-years (95% CI 510.3, 546.7) or 979 f/cc-years (95% CI 945, 1,013), depending on the regression equation used for the modeling. The lowest estimated exposure level observed for any mesothelioma case with diagnostic certainty was 68 f/cc-years. We confirmed that the estimation of potency factor for Québec chrysotile should not be expected to differ significantly from Darnton’s estimation for non-textile chrysotile (RM = 0.0014%), if better quality data for correspondence between impinger and fiber count measurements is involved. Among several estimations we made, the average meta-analytical mesothelioma potency factor for all types of chrysotile would be 0.0014% (95% CI 0.0010, 0.0.0018), and for non-textile chrysotile 0.0011% (95% CI 0.0008, 0.0015). Several estimations of a possible threshold that would correspond to non-elevated mesothelioma risk based on the Québec cohort were also made. The minimal cumulative exposure in mesothelioma cases demonstrated values that ranged from 4.8–6 MPCF-years, or 18–50 f/cc-years. Also, based on theoretical models, the threshold can be found at the level of 6.38 MPCF-years (standard deviation 2.6), or in the range from 35.9 f/cc-years (standard deviation of 15.4) to 65.9 f/cc-years (standard deviation of 29.6).